The Effect of the Combination of Baby Massage and Bach's Classical Music on the Quality of Baby's Sleep and Speech Development in Babies Aged 6-10 Months in Mother's School - Hanum, Parida; Saragih, Okta Ade Putri; Harefa, Novita Berlianti; Nasution, Nur Sofiah (GLOBAL HEALTH SCIENCE GROUP, 2024)
Infancy is a golden period for a child's growth and development so it needs special attention. One of the factors that influences a baby's growth and development is sleep and rest. Sleep is a form of adaptation for babies to their environment. Sleep is the main priority for babies, because this is when neuro-brain repair occurs and approximately 75% of the growth hormone is produced by the baby into its environment. The aim is to determine the effect of the combination of baby massage and Bach's classical music on the quality of baby's sleep and speech development in babies aged 6- 10 Months at Mother's School. The research method used was quasi-experimental with one group pre-test-posttest design. The population in this study was all babies aged 6-10 months of 30 people using a total sample of 30 babies. Data is collected using questionnaires and data analysis is done with univariate and bivariate analysis. Analysis results based on pairs of samples showed a p value of 0.037